Strategi E-Komunikasi Musisi Indie Bogor untuk Melawan Marginalisasi dalam Industri Musik - Agustina Multi Purnomo (Society, 2025)
This study examines how the e-communication-based marketing mix (7Ps) influences customer loyalty among Spotify listeners engaging with indie musicians from Bogor. Data were collected from 400 respondents using a quantitative approach and analyzed through Pearson correlation and multiple linear regression. The results indicate that all marketing mix elements significantly affect customer loyalty, with Promotion (? = 0.216) and People (? = 0.195) having the most substantial impact. Place was not statistically significant (p = 0.07), suggesting that geographical origin is becoming less relevant in fostering digital music loyalty. The Cooperation indicator recorded the highest mean score (M = 4.34) and showed a moderate positive correlation with the loyalty construct (R = 0.457), underscoring the importance of active listener participation. These findings suggest that emotional engagement, relational marketing, and symbolic branding are more influential in building loyalty within digital ecosystems than functional attributes such as pricing or product features. The study contributes to digital marketing and indie music research by proposing an expanded interpretation of the 7Ps framework that emphasizes emotional value creation, visual identity, and participatory community engagement. Practical recommendations are also offered for indie musicians, including emotional storytelling, consistent fan interaction, and visual branding strategies to strengthen listener loyalty. The study illustrates how indie musicians can resist platform-driven marginalization in highly competitive streaming environments.